Analysis of Antideformation and Antivibration Effect of Different Track Beds under Subway Train Vibration. (4th February 2022) - Zhang, Jin; Xi, Chuanhao; Sun, Yanhua; Li, Guangsheng; Liu, Junwei; Wang, Mengxue
Abstract : Running metro trains would inevitably influence the vibration deformation in the lower part of the roadbed structure. In order to study the effects of vibration, Qingdao metro line 3 tunnel was taken as the research background. The track coupling model was established using Abaqus-Simpack to analyze the train velocity, train axle load, and trackbed vibration forms for the vertical deformation of roadbed calendar effect to provide the reference in practical engineering design and deformation control. According to the analysis, influenced by the formation of Qingdao Metro Line 3, the time-history curve of the displacement excitation of the trackbed presents the distribution law of "large in the middle and small at both ends." According to the sensitivity analysis, the deformation of the trackbed is most obviously affected by the form of trackbed; the second was the influence of the axle load of the train. The speed change of the subway train presented relatively little influence on the displacement of the trackbed. Although the deformation control ability of the integral trackbed was better, its vibration reduction performance was poor. The vibration reduction performance of the rubber cushion floating trackbed was the best, followed by the steel spring floating trackbed.